2000
DOI: 10.1063/1.1312281
|View full text |Cite
|
Sign up to set email alerts
|

Helium-3 transport experiments in the scrape-off layer with the Alcator C-Mod omegatron ion mass spectrometer

Abstract: Abstract3 He gas was puffed from the wall into ohmic L-mode discharges of the Alcator C-Mod tokamak and the charged states were measured near the wall with the omegatron ion mass spectrometer. Analysis of the data shows that the concentrations of singly-and doubly-ionized helium near the wall are approximately equal. The electron temperature and density at the omegatron are too low to account for ionization of helium in the local flux tube, therefore the helium is ionized in a hotter region of the edge plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
1
4
1
Order By: Relevance
“…The characteristics of radial transport in the far SOL are essentially unchanged. We note that the above estimates of velocity are lower than those found through analysis of He ion transport in the SOL of C-Mod [27] as well as the analysis of fluctuation measurements using probes [28] and D α emission [29].…”
Section: Effect Of Changes In Core Confinementcontrasting
confidence: 62%
“…The characteristics of radial transport in the far SOL are essentially unchanged. We note that the above estimates of velocity are lower than those found through analysis of He ion transport in the SOL of C-Mod [27] as well as the analysis of fluctuation measurements using probes [28] and D α emission [29].…”
Section: Effect Of Changes In Core Confinementcontrasting
confidence: 62%
“…The study found that W ions in the far-SOL were not compatible with radial diffusive transport model and likely traveled convectively in the radial direction at about v r = 500 m s −1 . A similar conclusion was found much earlier on Alcator C-Mod during He-3 experiments [25]. The results of both these studies partially motivate the current study finding alternatives to diffusive radial transport in impurity SOL codes.…”
Section: Dlimsupporting
confidence: 89%
“…A recent investigation of helium transport in the Alcator C-Mod SOL with an ion mass spectrometer also indicates rapid cross-field transport in the far SOL. 24 It was found that in order to account for the relatively large ratio of singly-to doubly charged 3 He ions arriving at the wall, the cross-field diffusive and/or convective transport of helium must increase with distance from the separatrix. Near the wall, the required effective particle diffusion coefficient exceeded the Bohm level by more than two orders of magnitude, implying that an outward particle convection model may be a more appropriate description of the transport process.…”
Section: Discussionmentioning
confidence: 99%